2018
DOI: 10.1097/iae.0000000000001842
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Pigmented Lesions in Type 2 Idiopathic Macular Telangiectasia

Abstract: Our data may be useful for refining the current system for staging disease severity in MacTel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 33 publications
1
26
0
Order By: Relevance
“…The latter include pigmentary changes, possibly deriving from migrating RPEcells, neurodegenerative processes, cellular debris, and vascular alterations. [21][22][23] Although a correlation of hyperreflectivity with disease progression has been proposed, its functional relevance has yet not been evaluated. In this study, we used an approach that quantified hyperreflective changes in MacTel.…”
Section: Discussionmentioning
confidence: 99%
“…The latter include pigmentary changes, possibly deriving from migrating RPEcells, neurodegenerative processes, cellular debris, and vascular alterations. [21][22][23] Although a correlation of hyperreflectivity with disease progression has been proposed, its functional relevance has yet not been evaluated. In this study, we used an approach that quantified hyperreflective changes in MacTel.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of SRNV was estimated to 12.1% in one study investigating a sample of 1244 affected MacTel probands (Leung et al. ). SRNV may threaten central vision directly and responds to anti‐vascular endothelial growth factor therapy, whereas the basic neurodegenerative disease process does not (Kupitz et al.…”
Section: Discussionmentioning
confidence: 99%
“…These right-angled venules typically develop temporally. It has been suggested that a retinal Muller glial dysfunction or cell death may contribute to the formation of these venules [ 4 ]. Due to RPE migration into the retina along the course of the right-angled venules, retinal pigmented epithelial hyperplasia or clumps may be seen around the parafoveolar right-angled venules, and these pigments may extend into the inner retina to form irregular plaques enveloping these venules [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Due to RPE migration into the retina along the course of the right-angled venules, retinal pigmented epithelial hyperplasia or clumps may be seen around the parafoveolar right-angled venules, and these pigments may extend into the inner retina to form irregular plaques enveloping these venules [ 5 ]. This pigmentary “sheath” may also provide support for the abnormal blood vessels and increase the propensity of the tissue for fibrosis and tissue contraction [ 4 ]. Pigment clumping is initiated in the areas of outer retinal thinning and disruption, which suggests that atrophic changes in the photoreceptor layer may create a permissive environment for RPE transformation.…”
Section: Discussionmentioning
confidence: 99%